THE TEACHER'S ROLE IN INCREASING EMPLOYABILITY SKILLS OF THE DRAWING BUILDING ENGINEERING VOCATIONAL HIGH SCHOOL STUDENTS - Ridlo, Alrosyid; Jumintono, Jumintono; Achsan, Bambang Noor (Journal of Vocational Education Studies, 2018)
The process of preparing students on vocational education that includes the development of skills, competency, understanding, attitudes, work habits and the appreciation needed by workers to enable them to work successfully in their fields should be of interest to educators in vocational education institutions. Early observations of science and the emphasis on authentic assessment suggested that the 2013 curriculum for vocational high school is a renewal or innovation of the previous curriculum. The research is done through descriptive-qualitative re-search method. The population in this study is all teachers of vocational subject vocational competence of building drawing techniques in Bantul Regency. The technique of collecting data through an interview, observation, and documentation, data is analyzed to get a description about research object. The results showed that the selection of strategies and learning approaches should be studied closely, especially in relation to their relevance to learning missions, learning objectives, students' potential and characteristics, and environ-mental resources. Vocational teachers have at least four important roles in developing students' employability skills, namely the role of teachers as demonstrators, as mediators, as evaluators and as competent individuals. Implementation of the 2013 curriculum learning on the competence of building drawing techniques from several previous studies can be concluded to be implemented adequately.